1982
DOI: 10.1002/ana.410120308
|View full text |Cite
|
Sign up to set email alerts
|

Tetrabenazine has properties of a dopamine receptor antagonist

Abstract: Tetrabenazine is considered to act in a manner similar to reserpine to reduce the involuntary movements of tardive dyskinesia or Huntington's disease and to improve psychoses. We determined that tetrabenazine also has properties of a dopamine receptor antagonist by testing the ability of tetrabenazine to block the inhibitory effect of dopamine on prolactin secretion from rat anterior pituitary glands in vitro and to displace 3H-spiperone binding to dopamine receptors in the pituitary, corpus striatum, and a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 31 publications
3
20
0
1
Order By: Relevance
“…Although in vitro studies have shown that TBZ blocks dopamine D 2 receptors, as suggested by its ability to inhibit [ 3 H]spiperone binding to striatal membranes with a K i of approximately 2.1 × 10 -6 M, this affinity is 1000-fold lower than its affinity for VMAT2 [50,51]. Therefore, it is unlikely that the weak D 2 receptor antagonism is responsible for TBZ clinical effects, although it may be possibly involved in acute dystonic reactions rarely reported with TBZ [52].…”
Section: Scott (2000)mentioning
confidence: 91%
“…Although in vitro studies have shown that TBZ blocks dopamine D 2 receptors, as suggested by its ability to inhibit [ 3 H]spiperone binding to striatal membranes with a K i of approximately 2.1 × 10 -6 M, this affinity is 1000-fold lower than its affinity for VMAT2 [50,51]. Therefore, it is unlikely that the weak D 2 receptor antagonism is responsible for TBZ clinical effects, although it may be possibly involved in acute dystonic reactions rarely reported with TBZ [52].…”
Section: Scott (2000)mentioning
confidence: 91%
“…This mode of action was confirmed in our studies, because tetrabenazine prevented an increase in striatal dopamine content resulting from L-DOPA feeding to mice in our in vivo experiments (Table 2). Tetrabenazine also directly binds to and inhibits dopamine receptors in the brain (Login et al, 1982(Login et al, , 1983Reches et al, 1983). The brain concentrations of tetrabenazine achieved in our experiments were in the range 30 -60 nM (Table 2), which is sufficient to block VMAT-2 but not likely to inhibit striatal dopamine receptors in vivo [for related discussion, see Savani and Login (2007)].…”
Section: Dopamine Pathway Inhibitors and Treatment Of Hdmentioning
confidence: 99%
“…TBA, a synthetic benzoquinoline, depletes presynaptic storage of monoamines [20] and block post synaptic dopamine receptors [21]. Although it has been described as causing a dystonic reaction in very rare cases [22], the fact that it may produce TD has never been documented.…”
Section: Discussionmentioning
confidence: 99%